2015
DOI: 10.1007/s13277-015-4391-1
|View full text |Cite
|
Sign up to set email alerts
|

miRNA profiling in serum and tissue samples to assess noninvasive biomarkers for NSCLC clinical outcome

Abstract: In NSCLC, the altered expression of some miRNAs in primary tumor tissues has been correlated with diagnosis and prognosis, while the role of circulating miRNAs as cancer biomarkers is currently emerging. MiRNA expression profile through miRNA Affymetrix array was evaluated on a training set formed by the tumor component (n = 30 NSCLC serum, n = 11/30 tumor tissues) and the control component (n = 10 healthy serum and n = 11/30 noncancerous counterparts). Statistical analyses highlighted the following: a = 55 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…All datasets with references and reasons for excluding publications are summarized in Supplemental Table 1 (www.karger.com/?DOI=492343). Among the 5 included studies [22,23,24,25,26], 4 reported the OS [22,23,24,25] and 2 involved clinicopathologic parameters [23,26]. The characteristics and quality scores of the included studies are summarized in Supplemental Tables 2 and 3 (www.karger.com/?DOI=492343).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All datasets with references and reasons for excluding publications are summarized in Supplemental Table 1 (www.karger.com/?DOI=492343). Among the 5 included studies [22,23,24,25,26], 4 reported the OS [22,23,24,25] and 2 involved clinicopathologic parameters [23,26]. The characteristics and quality scores of the included studies are summarized in Supplemental Tables 2 and 3 (www.karger.com/?DOI=492343).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplemental Table 2 (www.karger.com/?DOI=492343) , 4 studies provided sufficient OS data for this meta-analysis and 2 studies achieved statistical significance correlating high expression of miR-133a with better survival outcome in NSCLC patients [22,23]; the remaining 2 studies reported no statistical significance in relation to miR-133a expression and survival time [24,25]. The combined HR based on the included studies was 0.561 (95% CI 0.396-0.794, p = 0.001, I 2 = 0%) (fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations